Barbastelle Bat Barbastella barbastellus (Schreber, 1774) ... - Hackländer, Klaus; Zachos, Frank E.; Russo, Danilo; Salinas-Ramos, Valeria B.; Ancillotto, Leonardo (Springer International Publishing, 2020)
(Uploaded by Plazi for the Bat Literature Project) No abstract provided. ...